The Description of Rubber Farmer Management in Sibiru Biru Sub-district, Deli Serdang Regency, North Sumatra and Its Response to the Introduction of Tapping Technology - Sumihar Hutapea; Tumpal HS Siregar; Suswati (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Production of smallholder rubber in Indonesia is still very low, in the range of 600 - 900 kg of dry rubber/ha/year. Many factors influence it, such as non-clonal plants still being managed. Other factors such as agronomic aspects which include efforts to shorten the TBM period either through agronomic technology (canopy management, fertilization, or ground water management) are still ignored by smallholder rubber farmers, due to the limited access, capital, and even the perception that rubber plant production will not experience significant increase through tapping systems. The main and first approach that must be taken at this time on smallholder rubber is a new technology in tapping and management. This activity was carried out by four meetings and training in the garden of one of the trainees. Trainees consisted of rubber farmers in Sari Laba Jahe Hamlet, which also included rubber farmers from Peria Ria Hamlet - Sibiru Biru Sub-district (Deli Serdang Regency, North Sumatra). The package of tapping technology introduction consists of 3 main elements, namely: 1) tapping starts from the upper left to the lower right in each tapping field, 2) the application of 2.5% stimulant concentration is carried out in the tapping groove every 4 tapping times and 3) tapping in a month can be combined with tapping 1/S to the top using a pacekung tapping knife. Thus, in a month done 4 times of double cut tapping, namely 1/2S (in the lower tapping area using an ordinary tapping knife, downward: pull method) + 1 / 4S (upward using a pacekung tapping knife: shearing method). The results of this activity show that it can increase the production, thereby increasing the volume of sap sold. This activity also shows that the dominant farmers manage 1 hectare of land, and with the planting year and planting material that have the potential to be increased in production through tapping systems. The survey results show that general knowledge about rubber cultivation is dominantly obtained from this activity.